The present image of society in the novels of national writers - Sujud, Arba'ie; Nik Muhamad Affendi, Nik Rafidah; Hamdan, Rahimah; Abu Bakar, Roslina (Human Resource Management Academic Research Society, 2021)
Literary works are sociocultural documents that display the image of a society concerning its environment. The objectives of the study was to identify and analyze the image of society in the novels of national writers. In this study, the researcher examined the culture of society then and now, which was described in the novels of national writers in Malaysia such as S. Othman Kelantan in his novel entitled Wajah Seorang Wanita (The Face of a Woman) and Ruang Perjalanan (Travel Space). Additionally, the novel Ranjau Sepanjang Jalan (Thorny Path) by Shahnon Ahmad. The culture that surrounded the society in Malaysia was related to the spirit of the neighborhood, family, and traditional medicine. The spirit of neighborhood among the Malay community in the village was still strong. They cared about each other. From the aspect of family, the Malay community in the village respected each other between family members. The wife would help the husband in continuing their family survival. However, in the novel Ruang Perjalanan, S. Othman Kelantan showed that there was a rift in family relationships when family matters were managed by the ‘Ciku” robot. This was symbolic of the modernization that was changing the values of tradition.